The effectiveness of Hello English application in improving students' learning motivation and reading skills - Amini, Siti Nuraisyah; Jamilah, Jamilah (LITERA, 2024)
Since English is not widely spoken in Indonesia, most students find it challenging to acquire the language, particularly when it comes to reading. Pupils exhibit low reading enthusiasm, boredom, and shyness. Therefore, teachers need to find a suitable teaching strategy. Hello English as a new application that promotes interactive and creative learning for users, especially students might be the solution. So, this study aims to find out the effectiveness of the Hello English application on students' learning motivation and reading skills at the tertiary level. This study is quasi-experimental research. Two classes were selected by the researcher to serve as the control and experimental groups using random sampling. Data is gathered by the researcher via questionnaires and tests. The independent sample t-test, descriptive statistics, and the N-Gain score formula were used to analyze the data. The findings indicate that the features in the Hello English program such as report cards, chat forums, games, dictionaries, and reading exercises boost students' motivation and reading skills. In conclusion, compared to conventional teaching methods, the Hello English application has a greater impact on students' reading skills, learning motivation, and both at the same time. These findings suggest that the features in the Hello English application were created to make learning English enjoyable for students and improve their comprehension of textual content.